Smectite in weathered hyaloclastite of the Shakotan Peninsula, Hokkaido, Japan: significance of clay mineralogy in engineering geology (Journal of Nepal Geological Society, 2000)
The occurrence and chemical composition of smectite in hyaloclastite from the Toyohama rock fall site of 10 February 1996 and the Oshoro Bay area were examined by using optical microscope, X-ray diffractometer, electron probe microanalyser and analytical transmission electron microscope. Frequently, smectite occurs as fillings and linings of pores in various forms, and sporadically as the replacement of volcanic glass in hyaloclastite. The analytical results show that smectite is of dioctahedral and Fe-rich type. Its compositional field varies extensively between montmorillonite and nontronite. Moreover, interlayer cations of smectite vary intensively in relation with the type of weathering in hyaloclastite. Na-smectite occurs characteristically in discoloured hyaloclastite affected by superficial weathering, whereas Ca- and K-smectite occurs dominantly in the hyaloclastite collected from the inner part of the rock mass. These features of smectite in hyaloclastite can be attributed to its formational and weathering environments. Mineralogical characterisation of hyaloclastite provides detailed information on engineering properties of this type of rock mass and rock materials.